Motivation and trust towards knowledge-sharing behaviour among staff at Sarawak State Library / Nur Azmira Mohd Noor and Nurul Nadirah Mohd Zuhana - Mohd Noor, Nur Azmira; Mohd Zuhana, Nurul Nadirah (2017)
Limited study regarding factors contribute to knowledge-sharing behaviour (KSB) has been directed in investigating whether motivation and trust are the predictors of knowledge-sharing behavior. More specifically, the researcher examined whether there is relationship between motivation (i.e. external extrinsic, introjected extrinsic, identified extrinsic and intrinsic) and trust (i.e. institution-based, competence-based and benevolence-based) with KSB. In many organizations, employees’ knowledge has been a critical resource, and if it is not properly shared, the organization will lose their most vital assets. However, sharing of knowledge depends on the individual itself. Some people may agree to share the knowledge and some may not mostly due to their personal reasons. Thus, this research is conducted to uncover the association between motivation and trust towards knowledge-sharing behaviour. Questionnaire was used to collect data from 46 staffs who work at Sarawak State Library. Descriptive statistics revealed that there is high level of motivation among staff. Moreover, multiple regression analysis also revealed that trust is the factor that influence knowledge-sharing behaviour among staff as well as the most dominant types of motivation towards knowledge-sharing behaviour among staff is identified motivation, not intrinsic motivation.